Epidemiological and pathological investigation of fowl aviadenovirus serotypes 8b and 11 isolated from chickens with inclusion body hepatitis in Spain (2011–2013). Issue 2 (4th March 2017) - Oliver-Ferrando, S.; Dolz, R.; Calderón, C.; Valle, R.; Rivas, R.; Pérez, M.; Biarnés, M.; Blanco, A.; Bertran, K.; Ramis, A.; Busquets, N.; Majó, N.
ABSTRACT: Inclusion body hepatitis caused by different fowl aviadenovirus (FAdV) serotypes has been described in several countries in recent years. In Spain, from the spring of 2011 to 2013, an increased number of outbreaks in broiler and broiler breeder flocks from different regions occurred. The objectives of the present work were to carry out the molecular characterization of FAdV strains from Spanish inclusion body hepatitis cases and to study the pathogenicity and viral dynamics of these strains in specific pathogen-free (SPF) chickens. A total of 52 inclusion body hepatitis clinical cases, including 45 from broiler farms and seven from broiler breeder farms, were analysed by conventional polymerase chain reaction and sequencing targeting the FAdV hexon gene. From these, 37 strains were classified as FAdV type 8b, while the remaining 15 were classified as FAdV types 11 ( n = 10), 2 ( n = 4) and 8a ( n = 1). In addition, two different FAdVs belonging to the genotypes 8b and 11 were used for experimental infection. Specific pathogen-free five-day-old birds were inoculated intramuscularly with a high (10 6.5 tissue culture infective dose (TCID)50 /ml) or low (10 4 TCID50 /ml) dose of the above-mentioned FAdVs. No mortality was observed in any of the experimental groups, and only one bird showed evident clinical signs. However, macroscopic and microscopic hepatic lesions, as well as viral DNA, were detected in birds from all infection groups. Inclusion bodies and viral DNA were also detected in the pancreas and in the small and the large intestine in some birds. Long-lasting shedding and transmission to contact birds were confirmed in all infected groups.